Response to short course androgenisation in late reported cases with micropenis - Huque, Mahmudul; Tofail, Tania; Ahmed, Tofail (IMC Journal of Medical Science, 2020)
Background and objectives: Micropenis is an abnormally short penis and its treatment should begin in infancy or in very early childhood. The present study investigated the response of short term testosterone therapy in late reported cases of micropenis. Methods: A total of 17 cases of micropenis between the age of 8 and 15 years were included in the study. Standard criteria for the diagnosis of micropenis were followed. All cases were treated with intramuscular testosterone 50 to 75 mg once every 21 days. Response to testosterone treatment was measured by the absolute and percent increment in stretched penile length (SPL). Response was considered adequate if final SPL crosses the average SPL for age. We also compared the response of treatment of cases reported before and after 11 years of age. Result: A total of 17 micropenis cases were included in the study. Out of total 17 boys, 10 were between 8 to 11 years (Group 1) and 7 were between 12 to 15 years (Group 2) of age. The mean pre-treatment SPL of 17 micropenis cases was 3.1±0.2 cm (CI: 2.83, 3.43 cm). The mean initial SPL of Gr1 and Gr2 was not significantly different (3.2±0.3 cm vs 3.0±0.1 cm; p>0.248). The mean post treatment SPL of 17 cases increased significantly (p<0.001) compared to their initial SPL. The range of percentage increment in SPL was 100%-400%. Higher testosterone doses were required in Gr2 cases compared to Gr1 (360±20.8 mg vs 260.7±38.5 mg). Conclusion: Micropenis in boys with palpable gonads responded to short term testosterone treatment in late reported cases and we termed these cases as simple micropenis. Ibrahim Med. Coll. J. 2020; 14(1): 1-4